Ética e interculturalidade no tratamento midiático das migrações: da produção dos conteúdos à recepção dos migrantes - Ravanello, Marília Moreira (2024)
The current work addresses the theme of migration, from the perspective of knowledge construction alongside migrants. The research takes a qualitative approach, encompassing both theoretical and empirical studies, in an attempt to answer the following question: considering that ethics and interculturality should be premises in the production of content on the theme of migration, how do migrants perceive the media's treatment of migration? The general aim of the study is to investigate the reception processes of media treatment of migrations by migrants from ethical and intercultural aspects. Four specific objectives were also defined: to understand the media's approach to migration and the media's representation of migrants based on previous research; to map and understand what is seen as ethical in communication on migration based on guides regarding the migration theme; to analyze the media consumption of migrant participants in the research; to understand how migration as mediation drives migrants' perception of the media's treatment of migration. In the theoretical research, representation is approached through the studies of Stuart Hall, engaging with discussions on stereotypes, racism, xenophobia, and related concepts; interculturality is explored through the works of Néstor García Canclini and Alejandro Grimson; and media ethics is examined through the studies of Stephen Ward, Nick Couldry, and Hugo Aznar. The empirical research was conducted on two fronts: a documentary research on communication guides about migrations, with ethical parameters analyzed based on the axes of Professional Performance and Content Production, and a reception study with migrants living in Brazil, using a semi-open in-depth interview as the methodological procedure, analyzed from the Migration as Mediation and Media Treatment of Migration axes. In the perception of migrants, discourses addressing otherness and the migrant other are predominantly constructed through stereotypical views, where the migrant is either victimized, marginalized, or seen as a threat. However, there are different ways to narrate migrations. The perspectives of the guides and the expectations of migrants point towards a mobilizing, more suitable, and committed communication that involves empathetic and sensitive conduct from communicators, combined with a critical engagement with the migration theme. Migrations need to be told considering the reasons that lead individuals to migrate, and situations need to be contextualized to avoid generalizations. Discourses need to consider a global perspective, viewing migrations as an ongoing process, as a contemporary social challenge transcending all countries, and as a human rights issue, alongside a local perspective that brings migrant individuals closer to the receiving society through stories about everyday life and the economic, social, and cultural contributions of migrants, highlighting their agency.